Rust-resistant coffee - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A spontaneous hybrid of robusta and arabica coffee plants has been discovered in New Caledonia in the western Pacific